ANALISIS MINAT MENABUNG NASABAH PT. BPR PRIMA MULTI MAKMUR - Djemuni; Mochammad Faisal Fadli (JEMBA : Jurnal Ekonomi Pembangunan, Manajemen dan bisnis, Akuntansi, 2021)
This study was conducted to determine the effect of customer interest in deciding to save at PT. BPR Prima Multi Makmur and to find out which factors are the most dominant in determining customer interest in deciding to save at PT. BPR Prima Multi Makmur. This research was conducted using a quantitative descriptive method, namely by analyzing respondents' answers with questionnaires that had been distributed. Then the results of these answers will be grouped based on existing criteria and the results of each statement answer are added up in the form of percentages then analyzed and draw conclusions from the research conducted. The results of the analysis using a Likert scale on thirty questionnaires for respondents' responses that have been distributed, the researchers set the indicator to get an average value of 3.07 in the "Neutral" category